Pengembangan dan Pemasaran UMKM Untuk Membangun Perekonomian Di Desa Mlorah Kabupaten Nganjuk - Nur Vita Dewan Tari; Nur Indah Fatmala; Neri Gareta Bintang Armevia; Kenneth Ephram Singarimbun; Rafael Octava Brilliante; Hendra Maulana (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The development of Micro, Small and Medium Enterprises (MSMEs) is an effort carried out by KKN-T MBKM UPNVJT students from group 5 of Mlorah Village. Those who are trying to hold an MSME Bazaar are